PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PICTURE AND PICTURE DALAM PEMBELAJARAN IPA SDN 06 JIRAK - Leonardus, Leonardus; Uliyanti, Endang; Margiati, K.Y. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is whether the use of the picture and picture model can improve the learning outcomes of students in the science learning 5th of Sekolah Dasar Negeri 06 Jirak, Kabupaten Bengkayang? This study was to describe the use of the model of picture and picture in the learning of natural sciences that could improve the learning outcomes of 5th grade students of Sekolah Dasar Negeri 06 Jirak, Kabupaten Bengkayang. The method used is descriptive method with the form of classroom action research. The study was carried out in 2 cycles. The assessment of the results of the learning plan from the first cycle is 3.37, and in the second cycle increased to 3.92. Assessment of the results of the implementation of learning from the first cycle is 3.38, and in the second cycle is 3. Assessment of the average student learning outcomes in the first cycle is 57.06, and in the second cycle is 78.24. Thus, research using the picture and picture model can improve learning outcomes in science learning of 5th grade students of Sekolah Dasar Negeri 06 Jirak, Kabupaten Bangkayang. Keywords: use, picture and picture, learning outcomes